INNER WHORLS OF GREGORYCERAS (AMMONITINA, PELTOCERATINAE) AS THE FIRST OCCURRENCE OF THE GENUS IN MEXICO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Two nuclei of Gregoryceras are described as the first record of the genus in Mexico. The occurrence in Mexico of the ubiquitous Tethyan genus Gregoryceras is interpreted as related to a major flooding episode that affected neritic shelves in the southern North-American plate.